The Modular-Rating System in Pedagogical Higher Educational Institutions as The Basis for The Individually Oriented Teaching of The Physics Teacher - Аbduvohid Uktamugli Umbаrov (Genius Journals, 2023)
This article describes the importance of the modular-rating system in pedagogical higher education institutions as the basis for the individually oriented teaching of the physics teacher
Keywords: Modular system; rating system; methodological competence; professional motive